Health Technology: Stretching Exercises Through an Application Prototype for Deskets With Cervicalgia: Pilot Study (European Journal of Social Science Education and Research, 2023)
Introduction: Neck pain is painful symptoms in the neck and shoulders in which might lead to withdrawal from work activity. Objective: This study aimed to assessment the effect of stretching exercises guided by a prototype app on neck pain in secretaries. Quantitative approach and case series study. A sociodemographic profile questionaire and the Visual Analogue Scale were accomplished to identify pain intensity. Result: Considering four participants in this study, all had fourty hours a week of work, with a mean age of 36.25 ± 8.65, single and white ethnicity 75%. The average pain intensity of the research participants before the intervention was 8.5±1.29 points, reducing to 4±0.81 points in the final evaluation. Conclusion: The results indicated that the prototype application with exercises for the cervical region was efficient in reducing the intensity of pain in the cervical region of the research participants.